Heroes. Season 3 [videorecording (DVD)] - Kring, Tim, 1957- (Universal Studios Home Entertainment, 2009)
Nathan creates a secret government program to hunt and capture people with superhuman abilities that gets out of his control, while those with abilities fight or flee. Peter struggles with his limited powers, and Hiro struggles with his lack of powers. Sylar searches for his father and has a run in with the government program, but makes a different decision than any of the other superpowered people.